Pengaruh Kualitas Pelayanan terhadap Kepuasan Konsumen Transportasi Maxim Bike pada Mahasiswa FKIP Universitas Nusa Cendana - Tansatrisna, Yohanis Alan; Data, Ari; Saragih, Fernando (Journal Economic Education, Business and Accounting, 2024)
This study measures Maxim Bike transportation satisfaction of FKIP students at Nusa Cendana University Kupang through five quantitative factors, namely physical evidence, reliability, responsiveness, assurance, and empathy, with a population of 10. 059 students from various study programs at FKIP Undana, using an incidental quantitative method that resulted in 140 samples, as well as multiple regression analysis through SPSS 22 which showed a positive and significant effect of physical evidence (t count 7.203), reliability (t count 2.187), responsiveness (t count 3.120), assurance (t count 6.628), and empathy (t count 5.494), with a calculated F value of 41.725 which confirms the positive impact of these parameters on customer satisfaction.